Arterial Intima-Media Thickness and its Relationship with Cardiovascular Disease and Atherosclerosis: A Possible Contribution of Medium-Sized Arteries - Bucciarelli, P.; Šrámek, A.; Reiber, J. H. C.; Rosendaal, F. R. (Thrombosis and Haemostasis, 2002)
The intima-media thickness (IMT) of the arterial wall, measured by B-mode ultrasonography, has been related to cardiovascular disease and atherosclerosis in many studies, most of which have considered carotid and common femoral arteries. No study has related the IMT of medium-sized arteries (e.g. brachial) to the atherosclerotic process. The aim of this study was to evaluate whether more peripheral arteries (e.g. brachial, superficial femoral and popliteal) represent a good model in studies of arterial wall IMT, as well as carotid artery. Twenty-six male patients with demonstrated coronary artery disease (median age 63 yrs; range 41–70) and twenty-four male controls (median age 62 yrs; range 53–74) were studied. The far-wall IMT of the common carotid, brachial, superficial femoral and popliteal arteries was measured by high-resolution B-mode ultrasonography. Its relationship with ischemic cardiovascular disease and the presence of atherosclerotic plaques in all the arteries was also evaluated. Mean IMT values were higher in patients than controls, more so in superficial femoral artery (IMT difference 0.08 mm [95% confidence interval 0.02 – 0.14]) and popliteal artery (0.08 [0.01–0.15]) than in common carotid artery (0.02 [−0.070.11]) or brachial artery (0.01[−0.01–0.03]). The difference did not change after adjustment for age. The prevalence of plaques was consistently higher in patients than controls, except for brachial artery, in which no plaque was found either in patients and controls. In all the arteries except brachial we found an association between increase in IMT and number of plaques. Age was strongly related to the presence of plaques in the carotid artery, and less markedly in superficial femoral and popliteal arteries.The brachial artery does not seem a good model to study atherosclerosis by ultrasound measurements of arterial IMT, whereas superficial femoral and popliteal arteries might be chosen for these studies besides carotid artery.
Keywords: Intima-media thickness; medium-sized arteries; B-mode ultrasound; atherosclerosis